Strategi Pengembangan Objek Wisata Kelabamadja di Kabupaten Sabu Raijua - Uly, Jaya Ayu Ningsih Kale; Fanggidae, Apriana H.J.; Kiak, Novi Theresia (Innovative: Journal Of Social Science Research, 2025)
This research aims to analyze the development strategy for the Kelab'ba Maja tourist attraction in Sabu Raijua Regency. using a qualitative descriptive approach method. This type of research is field research. The informants used in this research consisted of the Head of the District Tourism Office. Sabu Raijua, Head of Tourism, Tourism Management and Visitors / Tourists. Data was collected using field research techniques, interviews and documentation. The data sources in this research are primary and secondary data sources. Based on the research results, it shows that the development of the Kelabamadja tourist attraction in Sabu Raijua Regency has great potential with natural beauty and cultural richness that can attract tourists. However, so that this potential can be maximized, planned and sustainable management is very necessary. Key challenges such as accessibility, lack of facilities, and human resource training must be addressed through collaboration between the government and local communities. Support from the government and the use of technology and social media for promotion can help expand tourist attractions. Even so, attention to environmental and cultural sustainability is very important so that tourism growth does not damage existing natural and cultural attractions. By actively involving the local community, Kelabamadja tourism development can provide sustainable economic benefits and support the welfare of the local community.